1996
DOI: 10.1093/hmg/5.9.1245
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability and mutation analysis of hMSH2 and hMLH1 in patients with sporadic, familial and hereditary colorectal cancer

Abstract: To date, at least four genes involved in DNA mismatch repair, hMSH2, hMLH1, hPMS1 and hPMS2, have been demonstrated to be altered in the germline of patients with hereditary nonpolyposis colorectal cancer (HNPCC). Additionally, defective mismatch repair is thought to account for the observation of microsatellite instability (MIN) in tumors from these patients. The genetic defect responsible for the MIN+ phenotype in sporadic colorectal cancer, however, has yet to be clearly delineated. In order to better under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
116
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(126 citation statements)
references
References 28 publications
10
116
0
Order By: Relevance
“…No mutations in the hMSH2 gene, and only one somatic mutation in the hMLH1 gene, were found. Our results are in good agreement with previous studies that demonstrated that mismatch repair gene mutations are very rare in the RER+ sporadic forms of colon cancers: the hMSH2 gene was found to be altered in only nine out of 62 colon tumours (Børresen et al, 1995;Liu et al, 1995;Wu et al, 1997); the hMLH1 gene was found to be mutated in only eight out of 50 colon cancers (Liu et al, 1995;Moslein et al, 1996, Wu et al, 1997. Fourteen out of 21 (66.6%) pancreatic tumours were RER+, but 86% (12/14) were altered at a single locus out of the ten analysed; those samples should probably be classified as stable tumours.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…No mutations in the hMSH2 gene, and only one somatic mutation in the hMLH1 gene, were found. Our results are in good agreement with previous studies that demonstrated that mismatch repair gene mutations are very rare in the RER+ sporadic forms of colon cancers: the hMSH2 gene was found to be altered in only nine out of 62 colon tumours (Børresen et al, 1995;Liu et al, 1995;Wu et al, 1997); the hMLH1 gene was found to be mutated in only eight out of 50 colon cancers (Liu et al, 1995;Moslein et al, 1996, Wu et al, 1997. Fourteen out of 21 (66.6%) pancreatic tumours were RER+, but 86% (12/14) were altered at a single locus out of the ten analysed; those samples should probably be classified as stable tumours.…”
Section: Discussionsupporting
confidence: 93%
“…With regard to the sporadic forms of the same tumours, alterations of these genes have been shown in only a few cases of colon, endometrial and ovarian tumours with microsatellite instability (Børresen et al, 1995;Fujita et al, 1995;Katabuchi et al, 1995;Liu et al, 1995;Moslein et al, 1996;Wu et al, 1997). Methylation of the hMLH1 promoter region has been suggested to be an alternative mechanism of gene inactivation in sporadic colorectal tumours .…”
mentioning
confidence: 99%
“…A MMR gene germline mutation plus a second hit inactivating the wild-type allele in somatic cells (Hemminki et al, 1994) were thus established as the molecular basis fueling the mutator phenotype in HNPCCs; yet, the mechanism leading to sporadic MSI CRCs remained to be understood (Kinzler and Vogelstein, 1996). It turned out that in most sporadic MSI CRCs, mutations could not be identified (Moslein et al, 1996;Wu et al, 1997), leading to the speculation that non-mutational mechanisms were responsible for the defect. Thus, epigenetic changes in DNA were explored as the mechanism leading to gene silencing in cancer cells, alternate to mutational events.…”
Section: The Discovery Of Msimentioning
confidence: 99%
“…MSI is reported in 85 to 92% of CRC associated with HNPCC and in 10 to 15% of sporadic CRC. 17,[21][22][23] In 1996 Leach and colleagues 24 and Thibodeau and colleagues 25 reported the use of monoclonal antibodies directed against MSH2 and MLH1 in the immunohistochemical analysis of CRCs. Subsequent reports described immunohistochemistry (IHC) of MLH1, MSH2, and MSH6 in sporadic and HNPCC tumors with varying results.…”
Section: Immunohistochemistry (Ihc) Of Mismatch Repair (Mmr) Proteinsmentioning
confidence: 99%